Monetary policy and endogenous financial crises - Frédéric Boissay; Fabrice Collard; Jordi Galí; Cristina Manea (Deutsche Bundesbank, 2022)
We study whether a central bank should deviate from its objective of price stability to promote financial stability. We tackle this question within a textbook New Keynesian model augmented with capital accumulation and microfounded endogenous financial crises. We compare several interest rate rules, under which the central bank responds more or less forcefully to inflation and output. Our main findings are threefold. First, monetary policy affects the probability of a crisis both in the short run (through aggregate demand) and in the medium run (through capital accumulation). Second, a central bank can both reduce the probability of a crisis and increase welfare by departing from strict inflation targeting and responding systematically to fluctuations in output. Third, financial crises may occur after a long period of unexpectedly loose monetary policy as the central bank abruptly reverses course.
Keywords: E1; E3; E6; G01; 330; financial crisis; monetary policy